Fabrication and demonstration of ultra-compact 3D measurement module using silica-based planar lightwave circuit. (18th May 2020) - Katayose, Satomi; Kurata, Yu; Watanabe, Kei; Kasahara, Ryoichi; Itoh, Mikitaka; Watanabe, Daichi; Matsuo, Keigo; Hanano, Kazunari
Abstract: We fabricated an ultra-compact optical module using a silica-based planar lightwave circuit (PLC) for performing three-dimensional (3D) measurements. The module with a fiber, camera, lens, and flexible printed circuits is small enough to be attached to a tube with an inner diameter of 2.5 mm. The PLC is used as a fringe projector with a phase-modulation function and substrate for mounting the camera. A 3D measurement system based on a phase-shifting method was constructed using the module, and 3D profile measurements were performed on objects with thicknesses of 1.0, 2.0, and 3.0 mm. The experimental results indicated that the reconstructed shapes of the objects were clear enough for them to be recognized and the measurement variation was about 0.1 mm.